2006
DOI: 10.1016/j.bbi.2005.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Bereavement and marriage are associated with antibody response to influenza vaccination in the elderly

Abstract: Stressful life events exposure including bereavement, an event commonly experienced by elderly people, social support, marital status and satisfaction were examined in relation to antibody response to the annual trivalent influenza vaccination in an elderly community sample (N = 184). Antibody response was assessed at baseline, and at one and 12 months following vaccination. Taking into account baseline antibody titer, overall life events exposure and social support were not associated with response to any of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
2
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 52 publications
3
80
2
1
Order By: Relevance
“…Social support may be interpreted differently by these age cohorts and the relevance of different domains of support may differ. Other aspects of social support not measured in this study, such as marriage, may be more important for older adults, as suggested previously (Phillips et al, 2006).…”
Section: Age Depression Anxiety Social Support and Cortisolsupporting
confidence: 67%
See 1 more Smart Citation
“…Social support may be interpreted differently by these age cohorts and the relevance of different domains of support may differ. Other aspects of social support not measured in this study, such as marriage, may be more important for older adults, as suggested previously (Phillips et al, 2006).…”
Section: Age Depression Anxiety Social Support and Cortisolsupporting
confidence: 67%
“…It could be speculated that social support has differing relationships with physiological variables depending on age. For example social support has been associated with vaccination response in students (Gallagher et al, 2008) but not an older adult sample (Phillips et al, 2006). Social support may be interpreted differently by these age cohorts and the relevance of different domains of support may differ.…”
Section: Age Depression Anxiety Social Support and Cortisolmentioning
confidence: 97%
“…This detriment in neutrophil immunity was also accompanied by a higher cortisol/DHEAS ratio in the bereaved older adults relative to age-matched nonbereaved controls (Khanfer et al 2011). Bereavement in older adults has also previously been associated with a poorer antibody response to vaccination against the influenza virus (Phillips et al 2006). Changes in cortisol/DHEAS ratio with diminished immune function again suggest a potential mechanism through which stress could influence the body's defence mechanism against infection.…”
Section: Chronic Stress Ageing and The Immune Systemmentioning
confidence: 72%
“…An inadequate response and failure to provide required protection after vaccination, measured in terms of antibody titre, is indicative of a poorer immune response in the recipient. Unmarried older adults and those who had poor marital quality had a weaker antibody response to the influenza vaccination than happily married older adults (Phillips et al 2006). Life events stress and perceived stress were also related to a lower antibody response after vaccination against flu and meningitis in students (Burns et al 2002(Burns et al , 2003Phillips et al 2005), while greater social support enhanced antibody titres for some vaccine strains (Phillips et al 2005).…”
Section: Psychological Stress and Immunitymentioning
confidence: 87%
See 1 more Smart Citation